The chemical composition and manufacturing technology of glass beads excavated from the Hetian Bizili site, Xinjiang - Wang, Dong; Wen, Rui; Henderson, Julian; Hu, Xingjun; Li, Wenying (Springer Nature, 2020)
The Hetian Bizili site in Lop County, located on the southern route of the Silk Road in Xinjiang, China, was a trade and cultural hub between the East and the West in ancient times. In 2016, a large number of glass beads were unearthed from the 40 tombs excavated on this site. In this study we determined the chemical compositions and manufacturing technology of bodies and decorations of twelve glass beads from the M5 tomb of Bizili by using LA-ICP-AES, EDXRF, Raman Spectrometry, and SR-μCT. The chemical compositions of the beads were all Na2O–CaO–SiO2, with plant ash mainly used as a flux. Lead antimonate and lead stannate were used as the opacifying agents. We detected elevated levels of boron and high levels of phosphorus in some beads: this is discussed in the context of the type of flux used and the possible use of a P-rich opacifier. Some of the beads with high contents of aluminum may potentially come from Pakistan. In terms of manufacturing technology, the craftsmen made ‘eye’ beads in different ways and also trail decorated beads.